PENGUKURAN VIRTUAL REALITY MOTION SICKNESS MENGGUNAKAN VIRTUAL REALITY SICKNESS QUESTIONNAIRE DAN STABILITAS POSTURAL DALAM PELATIHAN BERJALAN PENGGUNA KAKI PROSTETIK - Nisrina Salsabila, Meivia
Gait abnormality and higher instability are two common problems experienced in prosthetic legs. The gait abnormality occurs in asymmetric normal legs and prosthetic legs, where the stability of prosthetic legs also decreased along with the fatigue after long walks. This instability increases the risk of falling and therefore gait training for prosthetic legs is needed. This study was conducted through an experiment with 12 participants (6 able-bodied and 6 transfemoral amputees). The participants were asked to walk on a treadmill with HMD VR (Head Mounted Display Virtual Reality). However, there are issues in the use of VR where the user can feel nausea, dizziness, and blurred vision due to an imbalance in the interaction between the visual movement information generated by VR and the vestibular movement information received by the user's organs called Virtual Reality Motion Sickness (VRMS). Therefore, it is necessary to review the VRMS of VR users using subjective measurements with the Virtual Reality Sickness Questionnaire (VRSQ) and objective measurements with postural stability. This training includes 40 minutes walking duration with a rest duration of 30 minutes and every 10 minutes measurement on the VRMS. In this study, footstep data from the motion capture system was used as a trigger for visual changes in the virtual environment. The footstep data then used to synchronize visual and vestibular movement signals, so that the symptoms of VRMS can be minimized. The results of this study indicate that there is a significant difference in VRMS as measured by the VRSQ along with the training duration. This also aligns with the measurement of the postural stability using the force plate AMTI. The results of this study will become recommendations to the design and development of gait training for prosthetic legs.